Phytotherapy for Acne Vulgaris - a Review - Kruczkowska, Adrianna; Pakuła, Mateusz; Urbański, Wojciech; Dolata, Natalia; Cebula, Agnieszka; Bulzacki, Emil; Stosiek, Aleksandra; Balcer, Bartosz; Kanturski, Andrzej; Liszka, Paweł (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Acne vulgaris, a chronic inflammatory skin condition, primarily affects adolescents and young adults, causing non-inflammatory and inflammatory lesions. Conventional treatments, including topical retinoids and systemic antibiotics, are effective but may lead to adverse effects, antimicrobial resistance, and high costs. These challenges have spurred interest in plant-derived compounds as potential safer alternatives. This review explores the efficacy and safety of these natural treatments. State of Knowledge: Research highlights the promise of plant-derived compounds such as polyphenols, essential oils, and herbal extracts in addressing acne pathogenesis. Epigallocatechin gallate from green tea inhibits sebum production, reduces inflammation, and shows antibacterial activity. Quercetin and essential oils like tea tree and lavender oils effectively reduce lesion counts and inflammation with minimal side effects. Extracts like Berberis vulgaris, mangosteen, and red ginseng show significant anti-acne effects. Despite these benefits, studies often feature small sample sizes and limited durations, necessitating further research. Summary: Plant-based treatments for acne vulgaris present effective, safer alternatives to conventional therapies, particularly for mild to moderate cases. These compounds reduce key factors like inflammation and bacterial colonization while improving patient adherence. However, larger, long-term trials are essential to confirm efficacy, optimize formulations, and establish their role in acne management.